Use of verbal de-escalation in reducing need for mechanical restraint in patients with psychotic disorders during non-voluntary transfers from home to the psychiatric emergency department - E. Miranda Ruiz; A. Gonzalez; P. Samos; M. Bellsola; A. Sabate; J. Leon; M.A. Jerónimo; V. Pérez-Solà; L.M. Martin; D. Corcoles (European Psychiatry, 2022)
Introduction Little is known about the need for mechanical restraint during non-voluntary transfers from patient’s homes to the psychiatric emergency department in patients diagnosed with Paranoid Schizophrenia. Although there is no evidence of its efficacy, one of the main tools used for the reduction of mechanical restraints is verbal de-escalation training.